PENGGUNAAN KAPUR DAN VARIETAS ADAPTIF UNTUK MENINGKATKAN HASIL KEDELAI DI LAHANSULFAT MASAM AKTUAL - Koesrini Koesrini; Khairil Anwar; Eva Berlian (Research Center for Biology-Indonesian Institute of Sciences, 2015)
High aluminum (Al) toxicity and soil acidity are the most important problems that cause low soybean productivity on actual acid sulphate soil. Soil quality improvement by using ameliorant and introducing adaptable variety are some options to increase soybean productivity in the soils. Field experiment was conducted to evaluate effect of using ameliorant and variety of soybean to increase its productivity onan actual acid sulphate soil of Simpang Jaya, Wanaraya, Barito Kuala District of South Kalimantan, during dry season of 2009. The research was arranged in a split-plot design with three replicates. The main plots were three soybean varieties, i.e. Lawit, Anjasmoro, and Argo-mulyo, while sub plots were five levels of lime i.e. K100, K80, K60, K40,K20.Result showed that liming improved soil quality and soybean yield. It significantly increased soil pH and reduced soil Al saturation. The liming also increased plant growth and yield variables (plant height, dry matter, root weight and yield) at three tested varieties. Anjasmoro was more adaptive than the others varietyon actual acid sul-phate soil.